Assessment of the implementation of the Long-term Strategy-2050 taking into account OECD approaches - B. K. Yessekina; G. A. Junusbekova; A. S. Kozhumov (Экономика: стратегия и практика, 2020)
This article discusses the issues of improving the system of state planning in the Republic of Kazakhstan, taking into account the OECD methodology. According to the authors, the priorities for assessing the effectiveness of the state planning system should include the development and use of a system of target indicators and a corresponding monitoring system. Based on the generalization of international and domestic experience in the field of strategic planning, the authors propose the use of the OECD methodology. As novelty, authors identified a system of indicators of “green growth”, analyze the dynamics of relevant indicators in the national statistics and substantiate recommendations to the Government on further improvement of the state planning system at the stage of its modernization.